Adoption of Sustainable and Human-Centered Explainable AI in Higher Education. An Extended UTAUT Perspective - Fine Masimba; Bester Chimbo; Kudakwashe Maguraushe (Politeknik Negeri Batam, 2026)
As Artificial Intelligence permeates higher education, concerns regarding its